2020
DOI: 10.1080/13696998.2020.1799816
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive assessment of patients with irritable bowel syndrome with constipation and chronic idiopathic constipation using deterministically linked administrative claims and patient-reported data: the Chronic Constipation and IBS-C Treatment and Outcomes Real-World Research Platform (CONTOR)

Abstract: Hunter (2020) Comprehensive assessment of patients with irritable bowel syndrome with constipation and chronic idiopathic constipation using deterministically linked administrative claims and patient-reported data: the Chronic Constipation and IBS-C Treatment and Outcomes Real

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 29 publications
0
20
0
Order By: Relevance
“…In addition, identifying patient subgroups in future studies in whom prescription drug therapy results in decreased healthcare utilization would also affect insurer treatment preferences, noting growing evidence of an association between treatment response and healthcare utilization in CIC (47). Our model suggests that insurers would have increasing preference toward drug therapy among subgroups of patients with greater healthcare utilization such as those typically referred to gastroenterology, contingent on the assumption that effective disease management (regardless of treatment specifics) might actually reduce healthcare utilization (7,34). We also found that clinicians should guide the choice between prucalopride and linaclotide and that an algorithmic approach to insurance coverage determinations is suboptimal, given variation in treatment preferences in sensitivity analysis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, identifying patient subgroups in future studies in whom prescription drug therapy results in decreased healthcare utilization would also affect insurer treatment preferences, noting growing evidence of an association between treatment response and healthcare utilization in CIC (47). Our model suggests that insurers would have increasing preference toward drug therapy among subgroups of patients with greater healthcare utilization such as those typically referred to gastroenterology, contingent on the assumption that effective disease management (regardless of treatment specifics) might actually reduce healthcare utilization (7,34). We also found that clinicians should guide the choice between prucalopride and linaclotide and that an algorithmic approach to insurance coverage determinations is suboptimal, given variation in treatment preferences in sensitivity analysis.…”
Section: Discussionmentioning
confidence: 99%
“…We tested an assumption that effective treatment of any kind (including OTC laxatives and not specific to prescription drugs) might result in fewer diagnostic tests, procedures, and healthcare visits, specifically to evaluate whether drug prices could even be supported on this basis (34,38,39). All costs were inflation adjusted to November 2020 using the US Bureau of Labor Statistics Consumer Price Index for healthcare and rounded to the nearest whole US dollar (40).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Focusing on stool frequency fails to recognize that most constipated individuals are bothered not by infrequent bowel movements but by symptoms suggestive of defecation difficulties, e.g. straining, need for manual maneuvers, passage of hard stools, and/or a sense of incomplete evacuation (4)(5)(6)(7)(8)(9). Thus, the subjective perception/ experience of what constitutes a normal bowel habit varies widely.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to its heterogeneous pathogenesis, there is no single effective therapy for IBS, and patients with similar symptoms can respond differently to the same treatment (7). Patients are likely to suffer from chronic symptoms; many patients have complex treatment histories spanning many years and have tried multiple different interventions (8).…”
Section: Introductionmentioning
confidence: 99%